Multifaceted Interactions Between Bile Acids, Their Receptors, and MASH: From Molecular Mechanisms to Clinical Therapeutics - Xuan Tang; Yuanjiao Zhou; Li Xia; Xiulian Lin; Yao Zhu; Menghan Chen; Jiayao Wang; Yamei Li (Molecules)
Metabolic dysfunction-associated steatohepatitis (MASH) represents a critical hepatic manifestation within the broader spectrum of metabolic syndrome. The pathogenesis of MASH is characterized by disruptions in lipid metabolism, inflammation, and fibrosis. Bile acids and their receptors are integral to the progression of MASH, primarily through their regulatory influence on the metabolic networks of the gut–liver axis. This review offers a comprehensive and systematic examination of the molecular mechanisms underlying bile acid biosynthesis, metabolic dysregulation, and receptor signaling anomalies in MASH. Furthermore, it explores the translational potential of these insights into clinical therapies. Bile acids and their receptors emerge as pivotal therapeutic targets for MASH. Future research should focus on an in-depth analysis of dynamic regulatory mechanisms and the optimization of multi-target combination therapies, thereby paving the way for significant clinical advancements.